Feelings of national identity of pubescent and adolescents in the province of Tarma and Lima - Vicuña Peri, Luis (2002)
The present study is a revision of the investigation made in 1987 for the IIPPSI of the UNMSM, with two samples of Púberes and teenagers, of the city of Tarma and others from Lima, in that then worked with a total sample of 921, in revision 2000 has worked with a 486 sample of púberes and adolescents altogether, also of both cities; in order to find out if the attitudes, perceptions, valuations and interests towards the indicators of national identity differ according to the regional origin, the sex and the level of training. For the data collection 4 scales with the Technique of Lickert were elaborated and for study 2000, it added 26 scales with the Technique of the Semantic Differential. In 1987 the regional origin does not raise differences, as if in the revision of the year the 2000 sample of Tarma presents/displays attitudes and I interest significantly greater than those of Lima. On the other hand sex maintains describing significant differences in favor of the women. With respect to the schooling and the feeling of national identity the inferior degrees present/display greater feeling of attachment than the students of superior scholastic degrees. Nevertheless he is advisable to emphasize that, the found differences happen within the category of positive tendency.